Kształcenie i praca nauczycieli w szkołach polskich oraz mniejszościowych na Górnym Śląsku w latach trzydziestych XX w. - Śliwak, Katarzyna (Acta Universitatis Lodziensis. Folia Historica, 2014)
Upper Silesia-border region, which had contact for centuries with Polish and German politics, culture and education. After it returned in the twenties of the twentieth century to the Poland Polish authorities had to deal with the problems of administrative, economic, social, cultural, educational. In the article the Author presents the issue related to the organization of Polish schools in Upper Silesia in the thirties of the twentieth century. With the establishment of new schools, there was a great demand for teaching staff, which, unfortunately, for the most part came from other regions of the country. Teaching staff had been subjected to the education of newly approved legislation. With regard to the education system in Poland, the Author presented the way of education, teacher training institutions, increase the qualifications of teachers in Silesia. Due to the nature of the border region, there was also the problem of this area of minority education, which tried to fight elected provincial governor and superintendent of Silesia, a supporter of rehabilitation, the unification of Upper Silesia with the rest of the country Michał Grażyński. The paper based on the memories of teachers will be presented to the problems of Polish students and teachers in minority schools.